A mini-review on population balance model for gas-liquid subcooled boiling flow in nuclear industry. (July 2021) - Hu, Guang; Ma, Yue; Zhang, Huang; Liu, Qianfeng
Highlights: Comprehensive work on the PBM in the gas–liquid subcooled boiling flow is examined. Typical various facilities for the subcooled boiling flow are summarized. Simulation results using different solving models are analyzed. Abstract: The application of the population balance model (PBM) in the gas–liquid subcooled boiling flow is of an emerging interest in the recent years. In this study, theoretical models, experimental work, numerical applications and new finds under the frame work of the Eulerian–Eulerian (EE) approach coupled with the PBM in the nuclear industry are reviewed systematically. Firstly, a comprehensive work on the sub-models of the PBM in the gas–liquid subcooled boiling flow condition is examined. It includes the boundary condition for the PBM and sub-models of the bubble condensation, bubble coalescence and breakup. Then, the typical experiment development and the main characteristics from 6 various facilities for the subcooled boiling flow are summarized. Furthermore, the simulation results using different solving models are analyzed. Finally, the study concludes with the further directions as well as the guidance in the subcooled boiling flow in the nuclear field and the related research.